Pengaruh Remunerasi dan Motivasi Kerja terhadap Kinerja Karyawan pada Kantor Balai Desa Tanjungsari Kecamatan Wanasari Kabupaten Brebes - Sri Ratih Handayani; Umrotun Mustika (Jurnal Strategik, 2020)
ABSTRAC The research method used is Quantitative Type research with a DescriptiveApproach, while the data collection methods used are interviews, observation, questionnaires and documentation. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing (t test, F test) and coefficient of determination test (R2)).  From the analysis, conclusions can be drawn: 1. Partially, the Remuneration variable (X1) has a positive and significant effect on employee performance (Y) at the Tanjungsari Village Hall Office,Wanasari District, Brebes Regency. Then the Work Motivation variable (X2)has a positive and significant effect on employee performance (Y) at theTanjungsari Village Hall Office, Wanasari District, Brebes Regency. 2. Simultaneously, the variables Remuneration (X1) and Work Motivation (X2) have a significant effect on employee performance (Y) at the Tanjungsari Village Hall Office, Wanasari District, Brebes Regency, shown by a significant value of <0.05. 3. The Remuneration Variable (X1) is the variable that has a dominantinfluence on employee performance (Y) at the Tanjungsari Village HallOffice, Wanasari District, Brebes Regency.Keywords: Remuneration, Work motivation, Employee performance